Investigation of the Quality of the 12 Most-Used Antibiotics Available in Retail Private Pharmacies in Rwanda - Thomas Bizimana; Védaste Kagisha; Jean Baptiste Nyandwi; Alain Katembezi Nyirimigabo; Raymond Muganga; Marie Françoise Mukanyangezi; Egide Kayitare (MDPI AG, 2022)
Using poor-quality antibiotics leads to increased risk of the development of microorganism-resistant strains, treatment failure, loss of confidence in health systems, and associated socio-economic impacts. The prevalence of poor-quality antibiotics has been found to be high in some of the Low and Middle-Income Countries (LMICs), but no data were available on the situation in Rwanda. This study was conducted to obtain data and inform health professionals on the quality of the 12 most-used selected antibiotics from private retail pharmacies in Rwanda. The investigation was conducted on 232 batches collected from randomly selected private retail pharmacies in all provinces of Rwanda, and concerned only with visual inspection and assay tests. Visual inspection was performed using a tool adopted by the International Pharmaceutical Federation (FIP) to identify manufacturing defects. An assay test quantified the Active Pharmaceutical Ingredient (API) in each collected batch using high-performance liquid chromatography (HPLC) coupled with an ultraviolet-visible (UV) detector, and the results were reported as the percentage content of the amount of APIs stated on the label. A total of 232 batches were analyzed, manufactured in 10 countries; the main country of manufacture was Kenya, with almost half of the batches (49.6%). The results of the visual inspection did not show the presence of counterfeit/ falsified antibiotics on the Rwandan market in this study but revealed weaknesses in labeling: more than 90% of the analyzed batches of the 12 antibiotics did not present the dosage statement on their label, and the complete list of excipients was missing in more than 20% of the analyzed batches. The assay test using HPLC confirmed the presence of APIs in 100% of the analyzed batches. However, moderate deviations from acceptable ranges of the API content defined by M. M. Nasr & C. M. Stanley in 2006 for erythromycin and the United States Pharmacopoeia 2018 for the other 11 molecules were found. The failure rate to meet the quality requirements in terms of the percentage content of active pharmaceutical ingredients declared on the labels was estimated at 8.2% in total, with 3.9% and 4.3% containing more and less than the amount of APIs stated on the labels respectively. The most-represented antibiotics on the Rwandan market were amoxicillin, co-trimoxazole and cloxacillin. No counterfeit antibiotics were found in this study. However, substandard batches with moderate deviations were found, suggesting that regular quality control of antibiotics is needed in Rwanda.